Strategic management and employee performance: a review and bibliometric analysis - Chan; Faerozh Madli; Haslinda Hassan; Umi Wahidah (Penerbit UMS, 2022)
Strategic management has become the most important practices that will help the organizations achieve their goals and employee performance will help organizations achieve their vision and mission. This paper conducted is to identify on how the strategy management effect on the employee performance in the organizations based on the scoping review of the relevant past studies paper. The Scopus database, VOS viewer software and Microsoft Excel has been used in this paper in order to analyse and determine the study of the paper review. With the large amounts of the research articles when scoping the data in Scopus database, the finalized amount that will be review is 177 papers that have been published between the year 2013 and 2022 and will analysed them by Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and bibliometric analysis. This paper has organized into the several parts which include the sections that describing the methodology, results and interpretations, discussion and future agenda. Thus, the research review carry out in this paper is a systematic literature review and a bibliometric analysis to identify the relationship between strategic management and employee performance.